If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = 3(x + -5) + 2 Reorder the terms: y = 3(-5 + x) + 2 y = (-5 * 3 + x * 3) + 2 y = (-15 + 3x) + 2 Reorder the terms: y = -15 + 2 + 3x Combine like terms: -15 + 2 = -13 y = -13 + 3x Solving y = -13 + 3x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = -13 + 3x
| 21x+31+9x+41=715 | | 6x^2+8x-20=4x^2+14x+16 | | (3/4)p=(4/5)p+(1/2) | | 21x+31+9x+41=712 | | 21x+31+9x+41=700 | | 10y-4=2y+20 | | y=3(2x-6)-10 | | 20x+30+5x+40=300 | | -5x+7=-23 | | 21x+31+9x+41=600 | | 7(x-5)=6x+35-13x | | 24-[5+7y-4(y+4)]=-5(5y-3)-[5(y-1)-19y+9] | | 8(8x)=6(6+10) | | -4=-x-5 | | -3-x=-8 | | Sin^2x+20sinx+91=0 | | 3/4x+5/x=1 | | 13=4(x-4)-(x-8) | | 28x^3-21x^2-7x=0 | | 18=-3x-4 | | 20x+30+5x+40=570 | | 20x+30+5x+40=574 | | -7-3x=-12 | | 10cos^2x-11cosx-6=0 | | 20x+30+5x+40=576 | | 20x+30+5x+40=581 | | 20x+30+5x+40=582 | | -3=-4-11x | | 20x+30+5x+40=579 | | -6x-1=-14 | | 20x+30+5x+40=580 | | d+32=108 |